The antiplaque efficacy of white tea extract mouthrinse - Dipika Kalyan Mitra; Palak Mahendra Shah; Hemang Harshad Shah; Silvia Victor Rodrigues; Chirag Javerchand Mehta (Wolters Kluwer Medknow Publications, 2016)
Objective: This study was conducted to assess the antiplaque efficacy of a mouthwash containing white tea. It also assessed the antibacterial properties of white tea against Prevotella intermedia (Pi), Porphyromonas gingivalis (Pg), and Aggregatibacter actinomycetemcomitans (Aa) in vitro. Materials and Methods: Forty-five subjects with healthy periodontium were randomly chosen and were divided into three groups and advised to use mouthwashes A, B, and C (Group A, white tea; Group B, distilled water [placebo]; Group C, chlorhexidine) for 4 days. They were advised to refrain from any kind of mechanical oral hygiene techniques. Plaque index (PI) was checked on day 1 and 5. In vitro testing for against Pi, Pg, and Aa against white tea extract was undertaken. Results: PI significantly increased from day 1 to day 5 (P < 0.01) in Groups A, B, and C. In inter-group comparison, there was a statistical significant difference between white tea mouthrinse group and placebo group, chlorhexidine group and placebo group and also chlorhexidine group and white tea mouthrinse group. However, chlohexidine showed superior antiplaque activity. In vitro test, white tea showed effective inhibition against all three bacterial strains Pi, Pg, and Aa at 1% concentration. Conclusion: White tea mouthrinse potently inhibits plaque formation although not as comparable to chlorhexidine mouthrinse. Hence, for those preferring herbal products, white tea mouthrinse is a good option.